Novel Opipramol-Baclofen Combination Alleviates Depression and Craving and Facilitates Recovery From Substance Use Disorder—An Animal Model and a Human Study - Bareli, Tzofnat; Ahdoot, Hadas Levi; Ben Moshe, Hila; Barnea, Royi; Warhaftig, Gal; Gispan, Iris; Maayan, Rachel; Rosca, Paola; Weizman, Abraham; Yadid, Gal (Frontiers in Behavioral Neuroscience, 2021)
Substance use disorders (SUDs) are associated with depression and anxiety, with the latter being one of the major factors in substance-seeking and relapse. Due to dose-dependent sedative side effects there is limited efficacy of baclofen treatment for SUDs. Here we suggest the use of a novel combination of opipramol and baclofen (O/B) which is known to attenuate anxiety and depression, for the facilitation of recovery from SUDs. Since both opipramol and baclofen have a common downstream signal transduction, their individual doses could be reduced while still maintaining the benefits of the combination. We tested the O/B combination in both animals and patients. Rats treated with O/B showed significant attenuation in craving behavior and in relapse rate during withdrawal from cocaine. In a double-blind, placebo-controlled pilot study, conducted in a residential detoxification center, 14 males and 3 females, aged 28-60 years were assigned to a study (n=6) and a placebo (n=11) group (placebo group: 40±10.5 years; O/B group 40±10.8 years). The participants completed scales measuring depression, anxiety and craving symptoms and provided saliva samples for stress hormone examination (cortisol and dehydroepiandrosterone-sulfate (DHEA-S)). Participants with polysubstance use disorder (PsUD) treated with O/B showed a reduction in cravings and depression and an increase in DHEA-S and in the DHEA-S/cortisol ratio. Our findings indicate a beneficial effect of O/B treatment. This study suggests a novel candidate for pharmacological treatment of patients with SUD and comorbid mood/anxiety disorders that may facilitate their rehabilitation.